2017
DOI: 10.1093/ptep/ptx012
|View full text |Cite
|
Sign up to set email alerts
|

Light-cone gauge superstring field theory in a linear dilaton background

Abstract: The Feynman amplitudes of light-cone gauge superstring field theory suffer from various divergences.In order to regularize them, we study the theory in linear dilaton background Φ = −iQX 1 with the number of spacetime dimensions fixed. We show that the theory with the Feynman iε (ε > 0) and Q 2 > 10 yields finite results. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…However light-cone superstring field theory suffers from contact term divergences which have not yet been understood fully [26][27][28][29]. A way to circumvent this has been suggested in [30]. also describe how our analysis can be easily extended to compactified string theories.…”
Section: Jhep11(2016)050mentioning
confidence: 99%
“…However light-cone superstring field theory suffers from contact term divergences which have not yet been understood fully [26][27][28][29]. A way to circumvent this has been suggested in [30]. also describe how our analysis can be easily extended to compactified string theories.…”
Section: Jhep11(2016)050mentioning
confidence: 99%
“…We shall now discuss how superstring field theory establishes this relation following the analysis of [26][27][28]. Alternative approach based on light-cone string field theory has been pursued in [2], but this suffers from the contact term ambiguities [90][91][92][93][94][95]. Ref.…”
Section: Wilsonian Effective Actionmentioning
confidence: 99%
“…While our approach will be based on a manifestly Lorentz covariant formulation of superstring field theory, there is an alternative approach, known as light-cone string field theory, that only manifestly preserves the SO(d − 1) subgroup of the SO(d, 1) Lorentz group. This approach has been successful for bosonic string theory [88,89], but there are various contact term ambiguities when we consider superstring field theory which have not been completely resolved [90][91][92][93][94][95][96].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper [13], we have shown that these divergences can be dealt with by dimensional regularization. In the case of type II superstrings, for example, one formulates a light-cone gauge superstring field theory in noncritical dimensions or the one whose worldsheet theory for transverse variables is a superconformal field theory with central charge c = 12 [14]. Although Lorentz invariance is broken by doing so, it does not cause so much trouble because the light-cone gauge theory is a completely gauge-fixed theory.…”
Section: Introductionmentioning
confidence: 99%